Spontaneous Pneumomediastinum an Unusual Complication of Covid-19 Infection in a Non-intubated Patient With Diffuse Bilateral Ground-glass Opacity: A Case Report of Progression of Disease During Self-isolation - Agin, Khosrow; Naghiloo, Tahereh (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Spontaneous pneumomediastinum or mediastinal emphysema is relatively a rare disease that occurs in viral and bacterial infections with the benign entity. Case: The patient was a 57-year-old man who, after a week of self-isolation at home, coming to the COVID-19 triage center of the hospital with severe shortness of breath. He was admitted to the Intensive Care Unit (ICU) due to acute respiratory failure. The patient was treated as the protocol designed and respiratory support with high flow nasal oxygen and Non-Invasive Positive Pressure Ventilation (NIPPV). Spontaneous pneumomediastinum was developed during viral pneumonia infection. The known risk factors included age, male sex, and abnormal laboratory finding. All the biochemical and hematological findings such as lymphopenia, thrombocytopenia, raised CRP, LDH, and ferritin were detected in our cases. They indicate a possible prognosis for the development of acute respiratory failure and adverse clinical outcomes. Conclusion: Spontaneous pneumomediastinum has usually a benign outcome in COVID-19 Pneumonia and its prognosis is related to background conditions in patients.